Platform Big Data Analytic Berbasis Apache Spark Bagi Pemula Dalam Menyusun Data Analysis Workflow - Daniel Jeremia; Henry Novianus Palit; Andre Gunawan (Jurnal Infra, 2022)
Data is a concrete foundation for decision-making. The development of technology, in turn, creates a problem in the number and complexity of data as it requires sophisticated methods to analyze. This calls for the need of big data analytics. Analyzing data quickly, simply, and robustly is now a very high requirement, especially for beginners.To combat this problem, a platform for big data analytics that is beginner-friendly is proposed in this research. This platform is created with the purpose of simplifying the process of analyzing data easily without the use of programming for beginners. Diagrams/workflows are designed to manipulate data in a drag-and-drop fashion to make it easier for beginners. Furthermore, this platform uses industry-leading technology such as Apache Spark to deal with the problems of big data analytic without being known by the user at all.A survey/demo of 12 people with 3 different backgrounds, namely commoners, beginners, and experts, is held. The obtained result indicates a positive experience in doing data analysis without programming. An average score of 4.4 out of 5 is given by the participants for how much this platform can simplify the work of data analysis. This big data analytic platform has a huge potential for beginners and professionals alike.